Time-lapse X-ray phase-contrast microtomography for in vivo imaging and analysis of morphogenesis - Moosmann, Julian; Ershov, Alexey; Weinhardt, Venera; Baumbach, Tilo; Prasad, Maneeshi S.; LaBonne, Carole; Xiao, Xianghui; Kashef, Jubin; Hofmann, Ralf (Nature protocols, 2014)
X-ray phase-contrast microtomography (XPCμT) is a label-free, high-resolution imaging modality for analyzing early development of vertebrate embryos in vivo by using time-lapse sequences of 3D volumes. Here we provide a detailed protocol for applying this technique to study gastrulation in Xenopus laevis (African clawed frog) embryos. In contrast to μMRI, XPCμT images optically opaque embryos with subminute temporal and micrometer-range spatial resolution. We describe sample preparation, culture and suspension of embryos, tomographic imaging with a typical duration of 2 h (gastrulation and neurulation stages), intricacies of image pre-processing, phase retrieval, tomographic reconstruction, segmentation and motion analysis. Moreover, we briefly discuss our present understanding of X-ray dose effects (heat load and radiolysis), and we outline how to optimize the experimental configuration with respect to X-ray energy, photon flux density, sample-detector distance, exposure time per tomographic projection, numbers of projections and time-lapse intervals. The protocol requires an interdisciplinary effort of developmental biologists for sample preparation and data interpretation, X-ray physicists for planning and performing the experiment and applied mathematicians/computer scientists/physicists for data processing and analysis. Sample preparation requires 9-48 h, depending on the stage of development to be studied. Data acquisition takes 2-3 h per tomographic time-lapse sequence. Data processing and analysis requires a further 2 weeks, depending on the availability of computing power and the amount of detail required to address a given scientific problem.
Gesehen am 09.10.2020